Structural behavior of FRCC layered deep beams reinforced with GFRP headed-end bars. (15th September 2021) - Bediwy, Ahmed; Mahmoud, Karam; El-Salakawy, Ehab
Highlights: Performance of GFRP-RC deep beams under single concentrated load was studied. The behavior of deep beams with a layer of FRCC material in the tie zone was investigated. Two types of fibers, basalt and steel, were used in the FRCC layer as well as headed-end GFRP bars. The provisions for strut-and-tie models in the Canadian codes for FRP-RC structures and the American code for steel-RC structures yielded reasonable capacity predictions. Abstract: In this study, seven concrete deep beams reinforced with glass fiber reinforced polymer (GFRP) headed-end bars were constructed and tested to failure. The beams had a rectangular section of 250 mm in width and 590 mm in depth with overall span of 1, 390 mm and were tested under three-point bending loading. The main test variables were the longitudinal reinforcement ratio and the incorporation of fiber-reinforced cementitious composite material in the tie zone. The arch action mechanism developed in all specimens as substantiated by the measured strains along the tie length. In addition, analysis of test results showed that the incorporation of basalt fiber pellets or steel fibers in the tie zone of the beam improved the behavior including the ductility and the load carrying capacity. It was also found out that the provisions for strut-and-tie model in the Canadian codes for FRP-RC structures and the American code for steel-RC structures yielded reasonable predictions to the load capacity of deep beams.